2008
DOI: 10.1074/jbc.m707348200
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Whisker Model of the Structure of Oxidized Cell Membranes

Abstract: An essential feature of the innate immune system is maintaining cellular homeostasis by identifying and removing senescent and apoptotic cells and modified lipoproteins. Identification is achieved through the recognition of molecular patterns, including structurally distinct oxidized phospholipids, on target cells by macrophage receptors. Both the structural nature of the molecular patterns recognized and their orientation within membranes has remained elusive. We recently described the membrane conformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
201
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(209 citation statements)
references
References 51 publications
6
201
0
2
Order By: Relevance
“…The structures of oxPC CD36 identified were established using a combination of cell binding studies and multiple distinct chromatographic and MS methods in conjunction with (i) results of numerous derivatization strategies to ascertain functional groups on isolated products, (ii) inference of structures of products that appeared plausible based upon MS results and known mechanisms of lipid oxidation and fragmentation, and (iii) de novo synthesis of each oxidized lipid. The identities of the oxidation products and synthetic standards were confirmed by demonstration that synthetic species recapitulate all biological, chemical, MS, and chromatographic characteristics of the lipids isolated from oxidized 1-palmitoyl-2-arachidonyl-sn-glycero-3-PC, oxidized 1-palmitoyl-2-lineoyl-sn-glycero-3-PC, and oxidized 1-palmitoyl-2-docosahexaenoyl-sn-glycero-3-PC (19,20,22,40,41). Liquid chromatographic/electrospray ionization/tandem MS analyses have demonstrated the generation of these species in lipoproteins oxidized by multiple distinct pathways in vitro (40), in atherosclerotic lesions in vivo (41), in retina following light exposure in dark-adapted rodents (20), and in cerebral tissues following ischemia-reperfusion injury (42).…”
Section: Structural Characterization Of Oxpc That Serves As a High Afmentioning
confidence: 94%
See 3 more Smart Citations
“…The structures of oxPC CD36 identified were established using a combination of cell binding studies and multiple distinct chromatographic and MS methods in conjunction with (i) results of numerous derivatization strategies to ascertain functional groups on isolated products, (ii) inference of structures of products that appeared plausible based upon MS results and known mechanisms of lipid oxidation and fragmentation, and (iii) de novo synthesis of each oxidized lipid. The identities of the oxidation products and synthetic standards were confirmed by demonstration that synthetic species recapitulate all biological, chemical, MS, and chromatographic characteristics of the lipids isolated from oxidized 1-palmitoyl-2-arachidonyl-sn-glycero-3-PC, oxidized 1-palmitoyl-2-lineoyl-sn-glycero-3-PC, and oxidized 1-palmitoyl-2-docosahexaenoyl-sn-glycero-3-PC (19,20,22,40,41). Liquid chromatographic/electrospray ionization/tandem MS analyses have demonstrated the generation of these species in lipoproteins oxidized by multiple distinct pathways in vitro (40), in atherosclerotic lesions in vivo (41), in retina following light exposure in dark-adapted rodents (20), and in cerebral tissues following ischemia-reperfusion injury (42).…”
Section: Structural Characterization Of Oxpc That Serves As a High Afmentioning
confidence: 94%
“…Although initially defined using PC molecular species, as outlined below, subsequent studies have shown that all classes of phospholipids examined thus far (PC, phosphatidylethanolamine, PS, and phosphatidic acid) harboring the high affinity motif for CD36 promote CD36-mediated recognition and phagocytosis (19,20,22,40,41). The structures of oxPC CD36 identified were established using a combination of cell binding studies and multiple distinct chromatographic and MS methods in conjunction with (i) results of numerous derivatization strategies to ascertain functional groups on isolated products, (ii) inference of structures of products that appeared plausible based upon MS results and known mechanisms of lipid oxidation and fragmentation, and (iii) de novo synthesis of each oxidized lipid.…”
Section: Structural Characterization Of Oxpc That Serves As a High Afmentioning
confidence: 99%
See 2 more Smart Citations
“…These reactive species react with the biomolecules such as nucleic acids (DNA and RNA), mostly membrane proteins and lipids, resulting to chain of reaction leading to lipid peroxidation, protein oxidation and Nucleic acid-base breakage (Parihar et al, 2007). ROS in membranes could cause alterations to the integrity, fluidity, permeability and biological functions of membranes; while they could generate in low density lipoprotein (LDL) proatherogenic and proinflammatory response as well as generates toxic products (Greenberg et al, 2008). One of the pathological conditions resulting from human exposure to radiations is anaemia, a blood disorder which affects all age groups especially the elderly, pregnant, lactating women and infants been more susceptible.…”
Section: Introductionmentioning
confidence: 99%